Yo reinaré : el Divino Niño en la comunicación publicitaria - Arango Lozano, Carlos Andrés; Sojo Gómez, Jairo Roberto ([Bogotá] : Editorial UTADEO, 2018)
The popular devotion to the Divino Niño (Divine Child) began in Bogotá, Colombia in the 1920's. The Christian icon has the legend the words "Yo Reinaré" (I will reign) at the base of the statue. The present research work studies the cases in which the image is commercially used in items such as toys, backpacks, watches, caps and the corporate identity of some commercial establishments. "The present book exposes the different uses of the image of the Divino Niño (Divine Child) as a graphic resource in advertising, generally associated with the popular and everyday and also deals with how it has become in our days an almost habitual phenomenon in the streets of Bogotá, an evidence of the extraordinary strength it has gainedʺ (HKB Translation)--Pages 19-20.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed November 7, 2019)
Keywords: Commercial art -- Colombia; Jesus Christ -- In art; Religion in advertising -- Colombia; Symbolism in advertising -- Colombia; Popular culture -- Colombia -- Religious aspects; Jesus Christ -- Cult -- Colombia; Colombia -- Religious life and customs; Electronic books